2016
DOI: 10.1152/ajpregu.00215.2015
|View full text |Cite
|
Sign up to set email alerts
|

Toward improved phosphorus efficiency in monogastrics—interplay of serum, minerals, bone, and immune system after divergent dietary phosphorus supply in swine

Abstract: Phosphorus (P) is of vital importance for many aspects of metabolism, including bone mineralization, blood buffering, and energy utilization. In order to identify molecular routes affecting intrinsic P utilization, we address processes covering P intake, uptake, metabolism, and excretion. In particular, the interrelation of bone tissue and immune features is of interest to approximate P intake to animal's physiology and health status. German Landrace piglets received different levels of digestible phosphorus: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 79 publications
4
40
0
Order By: Relevance
“…It is conceivable that the variation of PO 4 3− -P in the water prompted intrinsic responses of major players of P homeostasis. Indeed, studies in fish and mammals showed that the dietary P supply impacts on various tissue sites and body compartments such as gut, kidney and bone [45][46][47]. However, molecular specificities of associated regulators, transporters, and endocrine and paracrine signals are largely unknown and yet to be elucidated in African catfish.…”
Section: Mortality and Growth Performancementioning
confidence: 99%
“…It is conceivable that the variation of PO 4 3− -P in the water prompted intrinsic responses of major players of P homeostasis. Indeed, studies in fish and mammals showed that the dietary P supply impacts on various tissue sites and body compartments such as gut, kidney and bone [45][46][47]. However, molecular specificities of associated regulators, transporters, and endocrine and paracrine signals are largely unknown and yet to be elucidated in African catfish.…”
Section: Mortality and Growth Performancementioning
confidence: 99%
“…Lowering P demand could also have a major impact in achieving sustainable intensification in developing countries where the financial resources to purchase P fertilisers are limited [54,55]. Crops and animals demonstrate significant variation in phenotypic traits for soil P acquisition and P utilization depending on their environment [56,57], and a number of molecular breeding techniques are available and developing to progress desirable trait enhancement, including the use of gene markers, mutagenesis (e.g., CRISPR technology) and epigenetic inheritance [58][59][60][61]. For example, a mutant genotype of barley (Hordeum vulgare L.) with a lpa1−1 allele for low phytic acid generated seed with a 35% reduction in endosperm P and a 15% reduction in total seed P [62].…”
Section: Changing the Momentum Of The Systemmentioning
confidence: 99%
“…Moreover, the vitamin D system has proven to be one of the major molecular signaling cascades for dealing with dietary P restrictions [21]. Investigations on the regulation of P homeostasis revealed initial adaptation processes to divergent dietary P supply at the level of the parathyroid gland via parathyroid hormone (PTH) secretion with known implication on bone, kidney and intestine in pigs and broilers [1,22,23]. PTH, which primarily targets calcium serum levels, also showed short-term and long-term effects on intestinal transporter activity and the proliferation of enterocytes [24,25].…”
Section: Resultsmentioning
confidence: 99%